2021
DOI: 10.1002/cne.25166
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptides as potential modulators of behavioral transitions in the ant Cataglyphis nodus

Abstract: Age‐related behavioral plasticity is a major prerequisite for the ecological success of insect societies. Although ecological aspects of behavioral flexibility have been targeted in many studies, the underlying intrinsic mechanisms controlling the diverse changes in behavior along the individual life history of social insects are not completely understood. Recently, the neuropeptides allatostatin‐A, corazonin, and tachykinin have been associated with the regulation of behavioral transitions in social insects. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 125 publications
(164 reference statements)
0
16
0
Order By: Relevance
“…The ant brain, particularly synaptic relay stations in high-order integration centers along two visual pathways, undergoes plastic changes during the iLW phase (Grob et al 2017 , 2019 ; Rössler 2019 ; Stieb et al 2012 ). Furthermore, the transition from interior to exterior worker is accompanied by changes in the expression levels of neuropeptides playing an important role in behavior control (Habenstein et al 2021 ). This neuroplasticity supports the fact that novices perform visual learning and calibrate their visual guidance systems to acquire all information for orientation during foraging, e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ant brain, particularly synaptic relay stations in high-order integration centers along two visual pathways, undergoes plastic changes during the iLW phase (Grob et al 2017 , 2019 ; Rössler 2019 ; Stieb et al 2012 ). Furthermore, the transition from interior to exterior worker is accompanied by changes in the expression levels of neuropeptides playing an important role in behavior control (Habenstein et al 2021 ). This neuroplasticity supports the fact that novices perform visual learning and calibrate their visual guidance systems to acquire all information for orientation during foraging, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Cataglyphis ants use up to 3 days to perform learning walks (LWs) to acquire all information for orientation during foraging far away from the nest (Fleischmann et al 2016 , 2018b ; Stieb et al 2012 ; Wehner et al 2004 ; for a review: Zeil and Fleischmann 2019 ). The transition from interior to exterior worker is not only characterized by changes in behavior, but also leads to neuroplastic changes along visual pathways in the ant brain (Grob et al 2017 ; Habenstein et al 2021 ; Schmitt et al 2016 ; Stieb et al 2012 ; for reviews: Grob et al 2019 ; Rössler 2019 ). The iLWs include pirouettes, rotational body movements that are full or partial turns during which the novices stop several times (Fleischmann et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the neuroanatomical studies, analyses of neuropeptides and their localization in the Cataglyphis brain have recently been performed. For this, transcriptomal analyses were combined with mass spectrometry detection and localization to reveal the most comprehensive neuropeptidome that has been obtained from an ant's brain so far (Habenstein et al 2021a(Habenstein et al , 2021bSchmitt et al 2017). Both the neuroanatomical and neuropeptidome databases provide rich sources for future structure-function analyses in the brain of Cataglyphis ants, for example, to detect life-stage dependent changes in brain neuropils and neuromodulators, and for comparison of those attributes with other ant species.…”
Section: The Brain Of Cataglyphis and Sensory Pathways Associated Wit...mentioning
confidence: 99%
“…[22][23] More recently, evidence has also been reported that TRPs modulate both olfactory sensitivity and locomotor activity. 24,25 The insect MS neuropeptide inhibits visceral muscle contractions, while stimulating skeletal muscle contraction and enzyme secretion from digestive tissue. 26 In cockroaches, MS inhibits contractions of the foregut and hindgut.…”
Section: Introductionmentioning
confidence: 99%
“…TRPs have been shown to stimulate Malpighian tubules writhing in the locust Locusta migratoria , and stimulate diuretic activity in tubules of the locust Schistocerca gregaria 22–23 . More recently, evidence has also been reported that TRPs modulate both olfactory sensitivity and locomotor activity 24,25 . The insect MS neuropeptide inhibits visceral muscle contractions, while stimulating skeletal muscle contraction and enzyme secretion from digestive tissue 26 .…”
Section: Introductionmentioning
confidence: 99%